The US tiny house on wheels movement with respect to a building code and relevance to Australia. Issue 3 (2nd October 2018) - Wenban, Chris
ABSTRACT: Explanation of applicable US regulation for Tiny Houses on Wheels, the latest changes to that regulation and parallels to Australian regulations.